Defining the anterior nucleus of the thalamus (ANT) as a deep brain stimulation target in refractory epilepsy: Delineation using 3 T MRI and intraoperative microelectrode recording - Möttönen, T. (Neuroimage Clin, 2015)
BACKGROUND: Deep brain stimulation (DBS) is a minimally invasive and reversible method to treat an increasing number of neurological and psychiatric disorders, including epilepsy. Targeting poorly defined deep structures is based in large degree on stereotactic atlas information, which may be a major source of inconsistent treatment effects. AIM OF THE STUDY: In the present study, we aimed to study whether a recently approved target for epilepsy (anterior nucleus of thalamus, ANT) is visualized in clinically established 3 T MRI and whether ANT is delineated using intraoperative microelectrode recording (MER). We have especially focused on individual variation in the location of ANT in stereotactic space. We also aimed to demonstrate the role of individual variation in interpretation of MER data by projecting samples onto AC–PC (anterior and posterior commissure) and ANT-normalized coordinate systems. METHODS: Detailed analysis of ANT delineations in 3 T MRI short tau inversion recovery (STIR) images from eight patients undergoing DBS for refractory epilepsy was performed. Coronal and sagittal cross-sectional models of ANT were plotted in the AC–PC coordinate system to study individual variation. A total of 186 MER samples collected from 10 DBS trajectories and 5 patients were analyzed, and the location of each sample was calculated and corrected accordingly to the location of the final DBS electrode and projected to the AC–PC or coordinate system normalized to ANT. RESULTS: Most of the key structures in the anatomic atlas around ANT (mammillothalamic tract and external medullary lamina) were identified in STIR images allowing visual delineation of ANT. We observed a high degree of anatomical variation in the location of ANT, and the cross-sectional areas overlapped by study patients decreased in a linear fashion with an increasing number of patients. MER information from 10 individual trajectories correlated with STIR signal characteristics by demonstrating a spike-negative zone, presumably white matter layer, at the lateral aspect of ANT in ANT-normalized coordinate system as predicted by STIR images. However, MER information projected to the AC–PC coordinate system was not able to delineate ANT. CONCLUSIONS: ANT is delineated in 3 T MRI by visualization of a thin white matter lamina between ANT and other nuclear groups that lack spiking activity. Direct targeting in the anterior thalamic area is superior to indirect targeting due to extensive individual variation in the location of ANT. Without detailed imaging information, however, a single trajectory MER has little localizing value.